Double-lithium compound coated silicon-carbon composite material and preparation method thereof

By using dual lithium compounds to coat silicon-carbon composite materials in lithium-ion batteries, and using spray drying to deposit inorganic lithium compounds on the porous carbon surface and coat organic lithium compounds, the problems of high expansion of silicon-carbon materials and safety hazards of gaseous silanes are solved. , improves the circulation performance and safety of lithium-ion batteries and reduces costs.

CN119208564APending Publication Date: 2024-12-27GUIZHOU HUIYANG TECH INNOVATION RES CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411334285.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The high expansion of silicon carbon material in existing lithium-ion batteries leads to repeated repair of SEI films, reducing circulation and storage performance. The gaseous silane used at the same time has safety risks and high cost.

Method used

The silicon-carbon composite material is coated with a dual lithium compound, and the core is designed by the design of a core-shell structure, where the inner core is passivated silicon-carbon, and the outer shell is composed of inorganic lithium compounds and organic lithium compounds. It is prepared by spray drying and is first deposited on the porous carbon surface. Inorganic lithium compounds are coated with organic lithium compounds to reduce material defects and electron ion conductivity.

Benefits of technology

It significantly improves the circulation performance and safety of lithium-ion batteries, reduces expansion rate and material costs, improves the transfer rate of lithium-ion and the compatibility of electrolyte, and enhances the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208564A_ABST
    Figure CN119208564A_ABST
Patent Text Reader

Abstract

The invention discloses a double-lithium compound coated silicon-carbon composite material and a preparation method thereof, the composite material has a core-shell structure, the core is passivated silicon carbon, the shell is composed of a first shell layer and a second shell layer, the first shell layer is an inorganic lithium compound, and the second shell layer is an organic lithium coating layer. The preparation method comprises the following steps: adding liquid silane and porous carbon into an organic solvent, and gasifying and decomposing under negative pressure to obtain a silicon-carbon precursor material; and then coating an inorganic lithium compound on the surface through a liquid phase method, drying, adding the obtained material, uniformly mixing with an organic lithium compound, and carrying out spray drying to obtain the lithium ion battery positive electrode material. The obtained material is applied to a lithium ion battery, can improve the cycle performance, and is high in safety and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery material preparation, in particular to a dilithium compound-coated silicon-carbon composite material, and also relates to a preparation method of the dilithium compound-coated silicon-carbon composite material. Background Art

[0002] Silicon-carbon materials are composed of porous carbon and nano-silicon deposited in its pores. The porous structure of porous carbon itself reduces the expansion of nano-silicon, but it still has a full-charge expansion of up to 80-100wt%, which is much higher than the 25% full-charge expansion of artificial graphite. Although some researchers have reduced the full-charge expansion of silicon-carbon materials by increasing the pore volume or reducing the size of silicon grains, the improvement is not large. High expansion will cause repeated repair of the SEI film during charging and discharging, resulting in a decrease in its cycle performance and storage performance. To solve this problem, Chinese Patent Application No. 202410250702.9 discloses a method for preparing a silicon-carbon composite material based on a silane cracking method and its application. The preparation method is as follows: first, porous carbon of petroleum coke is prepared, and then silane gas and heteroatom gas are introduced for vapor deposition to obtain heteroatom-doped silicon-carbon precursor material; then passivation treatment and fluorination treatment are performed to obtain a silicon-carbon composite material. Although it relies on the high pore volume of petroleum coke porous carbon material to reduce expansion and improve cycle performance, the porous carbon itself has many defects, resulting in more side reactions, and the poor electronic and ionic conductivity will form SEI film during its charge and discharge process to consume lithium ions, resulting in no obvious improvement in the material's cycle performance.

[0003] Chinese Patent Application No. 202310116926.6 discloses a metal-doped amorphous carbon-coated silicon-carbon composite material, a preparation method and its application. Chinese Patent Application No. 202311025471.3 discloses a resin porous silicon-carbon negative electrode material, a preparation method and a lithium-ion battery. The silane used in the two patent applications is gaseous silane, which has great safety hazards and high cost. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned disadvantages and provide a material obtained for application in lithium-ion batteries, which can improve the cycle performance, has high safety and low cost. The silicon-carbon composite material coated with a lithium compound.

[0005] Another object of the present invention is to provide a method for preparing the dilithium compound-coated silicon-carbon composite material.

[0006] The invention discloses a dual lithium compound coated silicon carbon composite material, wherein the composite material presents a core-shell structure, the core is passivated silicon carbon, the shell is composed of a first shell layer and a second shell layer, the first shell layer is an inorganic lithium compound, and the second shell layer is an organic lithium coating layer.

[0007] A method for preparing a dilithium compound-coated silicon-carbon composite material of the present invention comprises the following steps: Step S1: adding liquid silane and porous carbon to an organic solvent in a mass ratio of liquid silane: porous carbon: organic solvent = 30-70:50:500, evacuating to 0.01-0.1Mpa, heating to 300-500°C for 1-6h, and then cooling to room temperature to obtain a silicon-carbon precursor material; Step S2: adding the inorganic lithium compound to an organic solvent to prepare a uniform solution with a mass concentration of 1-10% according to the mass ratio of inorganic lithium compound: dispersant: silicon-carbon precursor material = 5-10: 1-5: 100, then adding the dispersant and the silicon-carbon precursor material to mix evenly, spray drying (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.5kg / h, 2h), and carbonizing at 900-1200°C for 1-6h to obtain an inorganic lithium compound-coated silicon-carbon precursor material; Step S3: dissolve the organic lithium compound in an organic solvent to prepare a 10wt% solution according to the mass ratio of inorganic lithium compound coated silicon-carbon precursor material: organic lithium compound = 100: 5-15, then add the inorganic lithium compound coated silicon-carbon precursor material to disperse evenly, and spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.5kg / h, 2h) to obtain a dual lithium compound coated silicon-carbon composite material.

[0008] The above-mentioned method for preparing a dilithium compound-coated silicon-carbon composite material, wherein: the liquid silane described in step S1 is one of dimethylchlorosilane, propenyltrichlorosilane, triisopropylchlorosilane, propyltrichlorosilane, phenyldichlorosilane, diethyldichlorosilane or phenylchlorosilane.

[0009] In the above-mentioned method for preparing a dilithium compound-coated silicon-carbon composite material, the organic solvent is one of ethanol, ether, xylene, toluene or chloroform.

[0010] The above-mentioned method for preparing a dilithium compound-coated silicon-carbon composite material, wherein: the inorganic lithium compound described in step S2 is one of lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium cerium fluoride or lithium difluorophosphate.

[0011] In the above-mentioned method for preparing a dilithium compound-coated silicon-carbon composite material, the dispersant described in step S2 is one of sodium dodecyl sulfate, sodium tripolyphosphate, sodium hexametaphosphate or sodium pyrophosphate.

[0012] The above-mentioned method for preparing a dilithium compound-coated silicon-carbon composite material, wherein: the organic lithium compound described in step S2 is one of lithium trifluoromethanesulfonate, lithium perfluorohexanesulfonate, lithium nonafluoro-1-butanesulfonate or lithium perfluorobutylsulfonate.

[0013] Compared with the prior art, the present invention has obvious beneficial effects. It can be seen from the above technical scheme that the shell of the present invention is a double-layer coated core silicon-carbon material, the inner layer is an inorganic lithium compound, and the outer layer is an organic lithium compound. The inorganic lithium compound and the organic lithium compound are coated on the surface of the silicon-carbon precursor in sequence, and the inorganic lithium compound of the core is coated on the surface of the porous silicon-carbon material to reduce defects and improve the transmission rate of lithium ions. The organic lithium compound is coated on the outer layer, and has good compatibility with the organic electrolyte, reduces side reactions, and improves the initial efficiency and its storage performance. And the organic lithium compound is fluorinated lithium sulfonate with strong solvation ability, improves ion transmission and diffusion rate, and improves rate performance. The present invention generates nano-silicon by mixing liquid silane in porous carbon through a liquid phase method. The use of liquid silane has good uniformity, low boiling point under negative pressure, high safety, avoids the growth of silicon grains, reduces expansion, and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a SEM image of the dilithium compound-coated silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0015] Example 1 A method for preparing a dilithium compound-coated silicon-carbon composite material comprises the following steps: Step S1: 50 g of dimethylchlorosilane and 50 g of porous carbon were added to 500 g of ethanol, dispersed evenly, and added to a reaction kettle, evacuated to 0.05 MPa, heated to 400 ° C for 3 h, filtered, and then cooled to room temperature to obtain a silicon-carbon precursor material; Step S2: 8 g of lithium tetrafluoroborate was added to 160 g of dimethyl carbonate organic solvent to prepare a uniform solution with a mass concentration of 5 wt%, and then 3 g of sodium dodecyl sulfate and 100 g of silicon-carbon precursor material were added and mixed evenly, spray dried (inlet temperature 200° C., outlet temperature 80° C., flow rate 0.5 kg / h, 2 h), and carbonized at 1100° C. for 3 h to obtain an inorganic lithium compound-coated silicon-carbon precursor material; Step S3: 10 g of lithium trifluoromethanesulfonate was dissolved in 100 g of dimethyl carbonate organic solvent to prepare a 10 wt% solution, and then 100 g of inorganic lithium compound-coated silicon-carbon precursor material was added and dispersed evenly, and spray-dried (inlet temperature 200 ° C, outlet temperature 80 ° C, flow rate 0.5 kg / h, 2h) to obtain a dilithium compound-coated silicon-carbon composite material.

[0016] Embodiment 2: A method for preparing a dilithium compound-coated silicon-carbon composite material comprises the following steps: Step S1: 30 g of acryltrichlorosilane and 50 g of porous carbon were added to 500 g of ether organic solvent, evacuated to 0.01 MPa, heated to 300 ° C for 6 h, and then cooled to room temperature to obtain a silicon-carbon precursor material; Step S2: 5 g of lithium hexafluoroarsenate was added to 500 g of diethyl carbonate organic solvent to prepare a uniform solution with a mass concentration of 1 wt%, and then 1 g of sodium tripolyphosphate and 100 g of silicon-carbon precursor material were added and mixed evenly, spray dried (inlet temperature 200° C., outlet temperature 80° C., flow rate 0.5 kg / h, 2 h), and carbonized at 900° C. for 6 h to obtain an inorganic lithium compound-coated silicon-carbon precursor material; Step S3: Dissolve 5 g of lithium perfluorohexane sulfonate in 50 g of diethyl carbonate organic solvent to prepare a 10 wt% solution, then add 100 g of inorganic lithium compound-coated silicon-carbon precursor material and disperse evenly, spray dry (inlet temperature 200 ° C, outlet temperature 80 ° C, flow rate 0.5 kg / h, 2h) to obtain a dual lithium compound-coated silicon-carbon composite material.

[0017] Example 3 A method for preparing a dilithium compound-coated silicon-carbon composite material comprises the following steps: Step S1: 70 g of triisopropyl chlorosilane and 50 g of porous carbon were added to 500 g of xylene organic solvent, evacuated to 0.1 MPa, heated to 500 ° C for 1 h, and then cooled to room temperature to obtain a silicon-carbon precursor material; Step S2: 10 g of lithium hexafluorophosphate was added to 100 g of ethyl methyl carbonate organic solvent to prepare a uniform solution with a mass concentration of 10 wt%, and then 5 g of sodium hexametaphosphate and 100 g of silicon-carbon precursor material were added and mixed evenly, spray dried (inlet temperature 200° C., outlet temperature 80° C., flow rate 0.5 kg / h, 2 h), and carbonized at 1200° C. for 1 h to obtain an inorganic lithium compound-coated silicon-carbon precursor material; Step S3: dissolve 15g of an organic lithium compound in 150g of an organic solvent of ethyl methyl carbonate to prepare a 10wt% solution, then add 100g of an inorganic lithium compound-coated silicon-carbon precursor material and disperse it evenly, spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.5kg / h, 2h) to obtain a dual lithium compound-coated silicon-carbon composite material.

[0018] Comparative Example 1: A method for preparing a silicon-carbon composite material comprises: the difference from Example 1 is that organic lithium coating is not performed, that is, step S3 is not performed. The rest is the same as Example 1.

[0019] Comparative Example 2: A method for preparing a silicon-carbon composite material, comprising: Unlike Example 1, inorganic lithium coating is not performed, that is, step S2 is not performed. The rest is the same as Example 1 Comparative Example 3: A method for preparing a silicon-carbon composite material comprises: different from Example 1, step S1 does not use liquid silicon-carbon to dope porous carbon; that is, 100g of porous carbon is added to a fluidized bed, and an inert gas is introduced to exhaust the air in the pipe, and then monosilane gas is introduced at a flow rate of 300ml / min for 600min to obtain a silicon-carbon precursor material. Steps S2 and S3 are the same as in Example 1.

[0020] Test example 1: SEM test The dilithium compound-coated silicon-carbon composite material prepared in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the composite material prepared in Example 1 presents a granular structure with some microporous structures on the surface and a particle size between 5-10 μm.

[0021] Test Example 2: Physical and Chemical Performance Test The tap density and specific surface area of ​​the silicon-carbon composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested according to the national standard GBT-38823-2020 "Silicon Carbon". The powder resistivity of the material was tested by a four-probe tester; and the gas production of the powder material was tested (m1g of the powder material was added to deionized water to a concentration of 10wt%, soaked at 45°C for 48h, and the gas production V1 was tested, and the gas production V1 / m1*100% was calculated); the test results are shown in Table 1.

[0022] Table 1

[0023] It can be seen from Table 1 that the gas production and powder resistivity of the embodiment material are better than those of the comparative example. The reason is that the embodiment is doped with a double-layer lithium compound, which improves the coating integrity of the material and reduces the gas production. The coating material reduces the electronic and ionic resistivity of the material, thereby reducing the powder resistivity of the material.

[0024] Test Example 3: Button Battery Test The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-3 are used as negative electrode materials for lithium-ion batteries and assembled into button cells. The specific preparation method of the negative electrode material is: adding a binder, a conductive agent and a solvent to the composite material, stirring and slurrying, coating on a copper foil, drying and rolling. The binder used is LA132 binder, the conductive agent is SP, and the solvent is double distilled water. According to the composite material: SP: LA132: double distilled water = 80g: 15g: 15g: 300mL, a negative electrode sheet is prepared; a metal lithium sheet is used as the positive electrode; the electrolyte uses LiPF6 / EC+DEC, in which LiPF6 is the electrolyte, a mixture of EC and DEC with a volume ratio of 1:1 is the solvent, and the electrolyte concentration is 1.3mol / L; the diaphragm uses a composite film of polyethylene PE, polypropylene PP or polyethylene propylene PEP. The button cell is assembled in an argon-filled glove box. The electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell were tested, and the charging DCR (50% SOC) and cycle performance (0.2C / 0.2C, 100 times) were tested, as well as the expansion of the negative electrode sheet under full charge (100% SOC). The button cell was dissected to test its negative electrode sheet expansion rate. The test results are shown in Table 2.

[0025] Table 2 serial number First discharge capacity (mAh / g) First efficiency (%) DCR (Ω) Cycle performance (capacity retention rate, %) Full charge expansion (%) Example 1 1882.3 93.5 34.5 92.4 80.6 Example 2 1815.3 93.1 39.6 93.5 84.5 Example 3 1942.4 93.9 30.6 91.7 78.8 Comparative Example 1 1722.6 91.9 45.8 89.5 101.5 Comparative Example 2 1710.4 92.1 47.1 88.6 103.4 Comparative Example 3 1783.8 92.6 41.4 90.1 98.3 It can be seen from Table 1 and Table 2 that the embodiment is better than the comparative example in specific capacity, DCR, expansion and cycle performance. The reason is that the ion transfer rate of the material is improved by coating the surface of the material with organic lithium and inorganic lithium compounds, which reduces its irreversible capacity, reduces polarization, improves the initial efficiency and reduces DCR.

[0026] Test Example 4: Soft-pack battery test The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-3 were mixed with 90% artificial graphite as negative electrodes, and slurry mixing and coating were performed to prepare negative electrode sheets. 1 / 3 Co 1 / 3 Mn 1 / 3 A 2Ah soft-pack battery was prepared using LiPO4 (EC+DEC, volume ratio 1:1, electrolyte concentration 1.3 mol / L) as the positive electrode and Celgard2400 membrane as the separator.

[0027] 4.1 HPPC rate performance test: The rate performance of the soft pack battery was tested with a charge and discharge voltage range of 2.5 to 4.2 V and a temperature of 25 ± 3.0 °C. The resistance of the battery under different SOC conditions (90%, 70%, 50%, 30%, 10%) was tested by charging at 3C and discharging at 4.0C. The results are shown in Table 3.

[0028] Table 3

[0029] It can be seen from Table 3 that the impedance of the soft-pack batteries of silicon-carbon composite materials prepared by the materials of Examples 1-3 is significantly lower than that of Comparative Examples 1-3, that is, the charging time is shorter. The reason for this is that lithium ions need to migrate during the battery charging process, and the example materials have low powder resistivity and their dual lithium compounds improve the ionic conductivity of the materials, reduce impedance, and reduce DCR.

[0030] 4.2 Cyclic performance test: The obtained soft-pack battery was subjected to a cycle performance test under the following conditions: charge and discharge current 1C / 1C, voltage range 2.5-4.2V, cycle number 500 times, and its 500 times charging DCR (50% SOC, 1.0C) was tested. The test results are shown in Table 4.

[0031] Table 4

[0032] It can be seen from Table 4 that the cycle performance of the lithium ion battery prepared using the composite materials obtained in Examples 1 to 3 is significantly better than that of Comparative Examples 1 to 3. The experimental results show that the reason is that the example materials have low expansion and low powder resistivity, which reduces the lithium ions consumed by repeated repair of SEI during charging and discharging, and improves the cycle performance.

[0033] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A dual lithium compound coated silicon carbon composite material, wherein the composite material presents a core-shell structure, the core is passivated silicon carbon, the shell is composed of a first shell layer and a second shell layer, the first shell layer is an inorganic lithium compound, and the second shell layer is an organic lithium coating layer.

2. A method for preparing a dilithium compound-coated silicon-carbon composite material, comprising the following steps: Step S1: adding liquid silane and porous carbon to an organic solvent in a mass ratio of liquid silane: porous carbon: organic solvent = 30-70:50:500, evacuating to 0.01-0.1Mpa, heating to 300-500°C for 1-6h, and then cooling to room temperature to obtain a silicon-carbon precursor material; Step S2: adding the inorganic lithium compound to an organic solvent to prepare a uniform solution with a mass concentration of 1-10% according to the mass ratio of inorganic lithium compound: dispersant: silicon-carbon precursor material = 5-10: 1-5: 100, then adding the dispersant and the silicon-carbon precursor material to mix evenly, spray drying (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.5kg / h, 2h), and carbonizing at 900-1200°C for 1-6h to obtain an inorganic lithium compound-coated silicon-carbon precursor material; Step S3: dissolve the organic lithium compound in an organic solvent to prepare a 10wt% solution according to the mass ratio of inorganic lithium compound coated silicon-carbon precursor material: organic lithium compound = 100: 5-15, then add the inorganic lithium compound coated silicon-carbon precursor material to disperse evenly, and spray dry (inlet temperature 200°C, outlet temperature 80°C, flow rate 0.5kg / h, 2h) to obtain a dual lithium compound coated silicon-carbon composite material.

3. A method for preparing a dilithium compound-coated silicon-carbon composite material according to claim 2, wherein: The liquid silane described in step S1 is one of dimethylchlorosilane, propenyltrichlorosilane, triisopropylchlorosilane, propyltrichlorosilane, phenyldichlorosilane, diethyldichlorosilane or phenylchlorosilane.

4. The method for preparing a dilithium compound-coated silicon-carbon composite material according to claim 2, wherein: The organic solvent is one of ethanol, ether, xylene, toluene or chloroform.

5. The method for preparing a dilithium compound-coated silicon-carbon composite material according to claim 2, wherein: The inorganic lithium compound described in step S2 is one of lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium cerium fluoride or lithium difluorophosphate.

6. The method for preparing a dilithium compound-coated silicon-carbon composite material according to claim 2, wherein: The dispersant described in step S2 is one of sodium lauryl sulfate, sodium tripolyphosphate, sodium hexametaphosphate or sodium pyrophosphate.

7. The method for preparing a dilithium compound-coated silicon-carbon composite material according to claim 2, wherein: The organic lithium compound described in step S2 is one of lithium trifluoromethanesulfonate, lithium perfluorohexanesulfonate, lithium nonafluoro-1-butanesulfonate or lithium perfluorobutylsulfonate.

Citation Information

Cited By

  • Negative active material, preparation method thereof and lithium ion battery

    CN119852361A

  • Lithium ion battery negative electrode material and preparation method and application thereof

    CN121439766A